2007
DOI: 10.1007/s00221-007-1016-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bimanual dynamics are learned without interference

Abstract: Dynamic learning in humans has been extensively studied using externally applied force fields to perturb movements of the arm. These studies have focused on unimanual learning in which a force field is applied to only one arm. Here we examine dynamic learning during bimanual movements. Specifically we examine learning of a force field in one arm when the other arm makes movements in a null field or in a force field. For both the dominant and non-dominant arms, the learning (change in performance over the expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
(35 reference statements)
4
20
0
4
Order By: Relevance
“…Indirect evidence for the relationship between gain and delay comes from interference studies. The interference paradigm shows that both successive (Krakauer et al 1999; Tong et al 2002; Caithness et al 2004) or simultaneous (Tcheang et al 2007; Sing et al 2009) presentations of competing tasks disrupt learning and consolidation. Delayed visual feedback disrupts adaptation to visuomotor rotation and displacement (Held et al 1966; Honda et al 2012), but gain and rotation were not found to interfere with each other (Prager and Contreras-Vidal, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence for the relationship between gain and delay comes from interference studies. The interference paradigm shows that both successive (Krakauer et al 1999; Tong et al 2002; Caithness et al 2004) or simultaneous (Tcheang et al 2007; Sing et al 2009) presentations of competing tasks disrupt learning and consolidation. Delayed visual feedback disrupts adaptation to visuomotor rotation and displacement (Held et al 1966; Honda et al 2012), but gain and rotation were not found to interfere with each other (Prager and Contreras-Vidal, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this latter prediction was confirmed. When a robotic device was used to create lateral perturbations in one hand, online corrections in the one-cursor task were shared across the two hands [32] (see also Refs [33,34]). Interestingly, this behaviour was observed even if visual feedback of the cursor(s) was absent during the movement.…”
Section: Task-dependent Feedback Controlmentioning
confidence: 99%
“…As regards uncoupled scenarios, Tcheang et al (2007) studied force field adaptation in a non-symmetric bimanual task, in which subjects made reaching movements with both hands, moving in separate, non-overlapping workspaces and toward different targets, under the effect of force fields with either equal or opposite orientations. They found no differences in the ability of the two hands to adapt to both types of force fields, and no evidence of interference between the two learning processes.…”
Section: Introductionmentioning
confidence: 99%